Implementation of combined hydrogen aqua electrolyser-fuel cell and redox-flow-battery under restructured situation of AGC employing TSA optimized PDN(FOPI) controller - Arindita Saha; Puja Dash; Tirumalasetty Chiranjeevi; Naladi Ram Babu (Journal of Taibah University for Science)
This work addresses the automatic-generation-control of multiple-area and sources under a restructured-situation. Sources within area-1 represent geothermal power plant, thermal, and gas, and area-2 sources represent thermal, hydro, and wind. An original endeavour is brought about to execute a controller with an admixture of proportional-derivative with filter (PDN) (integer-order) besides fractional-order proportional–integral (FOPI). Examination manifests excellence of PDN(FOPI) over integer order controllers likely integral, proportional–integral, proportional–integral–derivative-filter from perspective concerning depleted status of peak aberrations, extent-of-oscillations, and duration of settlement. To attain the controller’s attributes bioinspired meta-heuristic tunicate swarm algorithm is exercised. The occurrence of renewable sources makes arrangements meaningfully improved related to base thermal-gas-hydro arrangement. The action of hydrogen aqua electrolyzer-fuel cell and redox flow battery is examined using a PDN(FOPI) controller, providing noteworthy outcome in dynamic performance. The analysis is conducted under all the schemes of restructured situations.